The Occurrence(s) of Septicaema epizootica in Bali Cattle at Kupang Regency in 2005 - 2011 - Yohanes T.R.M.R.; Theresia, F.I.M.D.M. (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2012)
Septicemia epizootica (SE) disease in Bali cattle have occurred in the province of East Nusa Tenggara (NTT). The development of this disease should always be monitored to evaluate the existence and success of the treatment and the prevention that has been done. The purpose of this paper is to evaluate the presence of SE disease in Bali cattle in 2005-2011 in Kupang Regency, NTT. Data obtained from the field and practical work in Kupang District Veterinary Office. Septicemia epizootica disease in cattle was always found in Kupang district by the number of deaths 55, 28, 25, 30, 26 , 72 and 117 heads in the year 2005, 2006, 2007, 2008, 2009, 2010 and 2011, respectively. Clinical signs of bali cattle suffered SE were decreased appetite and weight gain, lethargy and eventually death. Before the dead the cattle showed symptoms of clinical symptoms level increased body temperature, submandibular edema that can spread to the chest area, and respiratory symptoms with snoring sound or discharge of mucus from the nose. Vaccination program can not be implemented optimally because difficult geographical conditions in the reach and kept cattle in not benign. Diagnosis of SE taken at the NTT should be followed up with laboratory tests and for the prevention and control of the SE is better to treat the policy of vaccination, so that all cattle and other susceptible animals can be vaccinated. Keywords: Septicemia epizootica, Bali cattle, Kupang regency, snoring, vaccine